Child with community acquired staphylococcal pneumonia complicated by bilateral pneumothorax - Kumar, Magesh; Jain, Chirag (International Journal of Contemporary Pediatrics, 2020)
Community acquired Methicillin-resistant Staphylococcus aureus (MRSA) pneumonia usually present in children with some comorbidity and may have fulminant course in these children. In this case report authors have described a healthy child with MRSA pneumonia complicated by bilateral pneumothorax.